Financial Stability In An Evolving Regulatory And Supervisory Landscape - Xiao, Yingbin (Washington, D.C. : International Monetary Fund, 2013)
This paper runs qualitative and quantitative analyses of the financial soundness of Danish banks. Helped by a series of Denmark's financial policy initiatives, banks have made progress in improving financial stability. However, vulnerabilities remain. To mitigate risks, banks should continue to build more robust capital and liquidity buffers, and enhance further the transparency of disclosures. The flexibility embedded in EU regulations should be used to design strong prudential policies, treating Basel III and the CRD IV regulations as floors. Crisis prevention and management could be further strengthened by phasing out gradually deferred-amortization mortgage loans and introducing risk-adjusted deposit insurance premia.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet